TEACHING INNOVATION IN ENGINEERING: A STUDENTS AND TEACHERS’ LEARNING INTEGRATION PROGRAMME - Justo Estebaranz, Jesús (2014)
This paper presents an experience in teaching innovation whose goal is to improve learning in engineering students and teachers (University of Seville, Spain). This innovation offers students a realistic, professional and updated vision of the contents, allowing them a direct contact with the problems posed by the knowledge and competence inherent to a subject, using facilities and resources at a high-tech research laboratory. It is an assessment-research case study that uses quantitative and qualitative methodologies. The results show improvement in the students’ learning processes as well as their high satisfaction; it also highlights the difficulties found. The teachers acknowledge this innovation process as a strategy to learn to teach and create improvements for the program.